Parasitic infection: a recurring phenomenon in Malaysia - Nissapatorn, V.; Lim, Y.A.L.; Jamaiah, I.; Rohela, M.; Anuar, A.K. (2007)
A total of 255 patients including 179 (70.2) of non-HIV and 76 (29.8) HIV-infected patients were recruited in this descriptive study. The subjects was significantly found to be male Chinese (157; 61.6 vs 74; 47.1) followed by female Malays (98; 38.4 vs 35; 35.7) (p<0.05). The majority of subjects (124; 48.6) were in the age group of 21-39 years, however, no statistical difference was found between the various age groups (p>0.05). Overall seroprevalence of latent Toxoplasma infection was 82/183 (44.8) being; 3 (3.7) positive for IgM, 74 (90.2) for IgG, and 5 (6.1) for IgG and IgM antibodies. The prevalence was more relatively found in the Chinese (28; 15.3) and Malays (27; 14.8) than others (p<0.05). While, 23/76 (30.3) of HIV-positive patients were shown Toxoplasma seropositivity. The majority of these subjects (138/181; 76.2) were significantly asymptomatic (p = 0.000), while the others were clinically evident cases of toxoplasmosis. Of this, 37 patients were included in differential diagnosis relating to ocular diseases and only 4 patients were confirmed as having ocular toxoplasmosis. Toxoplasmic encephalitis (TE) was based on presumptive diagnosis, particularly found in 5 patients with AIDS. Seventeen patients were clinically diagnosed as having malaria being; 8 for P. vivax, 4 for P. falciparum, 3 for P. malariae, and 2 for mixed infections. All cases resolved satisfactorily after treatment with antimalarial drugs. Other important emerging parasitic diseases were also detected in these patients including amebiasis (2), blastocystosis (1), cryptosporidiosis (1), filariasis (1), and giardiasis (2) during the time of this study.